Risk assessment in adoption of mushroom cultivation as a subsidiary occupation - Goel, Rajni; ., Rachna; Sodhi, GP S (Mushroom Research, 2019)
India faces the most challenging task of transforming the fast emerging agricultural technologies to sustain the increase in farm productivity and economic viability of farming. A variety of extension programmes are implemented for creating awareness, educating and motivating the farmers, farmwomen and rural youth to adopt and manage the new agricultural technology in the fields/homes. This is one of the major contributing factors for making India a food surplus country (Samanta and Gowda, 2003). Although, per hectare productivity has increased since early 1970s, per farm family income has decreased due to sub-divisions of land holdings and rising cost of cultivation (Source: Statistical abstract of Punjab, 2010, Department of Agriculture, Govt. of Punjab, 2005).Â With increasing pressure on land for more production per unit area through adoption of modern technologies and use of capital inputs, marginal and small farmers are unable to keep pace with the rapid technological advances in crop production, therefore, extension endeavours are directed towards net income increase from agricultural and allied activities. Mushroom production as a subsidiary occupation has a great potential for sustaining rural livelihood because of abundantly available recyclable agro-based like cereal straws, enormous domestic market, cheap man power, congenial climate, strong technical base and government support (Kaul, P.L. 1999). Krishi Vigyan Kendra, Patiala is actively engaged in imparting trainings in mushroom 49 cultivation to the farmers/farm women and rural youth. During 2005-06 to 2009-10, seven such vocational training programmes were organized in which 146 trainees successfully completed these training programmes (5-days duration). Despite all the favourable conditions, mushroom farming is not spreading fast. There are certain inherent problems or bottlenecks which hamper fast spread of mushroom farming in India. So, the present study was conducted with the objectives, (i) To find out the impact of vocational trainings in terms of adoption and continuation of mushroom production units, (ii) To assess the knowledge gain of the participants of training programmes, and (iii) To find out the problems/constraints in adoption of mushroom farming and continuation of such units.